Alternatives of mesenchymal stem cell-derived exosomes as potential therapeutic platforms - Lee, Sihun; Jung, Se Young; Yoo, Donghyeon; Go, Dabin; Park, Ji Yeong; Lee, Jong Min; Um, Wooram (Frontiers in Bioengineering and Biotechnology, 2024)
With outstanding therapeutic potential in the tissue regeneration and anti-inflammation, mesenchymal stem cell-derived exosomes (MSC-EXOs) have emerged as a prominent therapeutic in recent. However, poor production yield and reproducibility have remained as a significant challenge of their practical applications. To surmount these challenge, various alternative materials with stem cell-like functions, have been recently investigated, however, there have been no comprehensive analysis in these alternatives so far. Here, we discuss the recent progress of alternatives of MSC-EXOs, including exosomes and exosome-like nanovesicles from various biological sources such as plants, milk, microbes, and body fluids. Moreover, we extensively compare each alternative by summarizing their unique functions and mode of actions to suggest expected therapeutic target and future directions for developing alternatives for MSC-EXOs.